2000
DOI: 10.1149/1.1393303
|View full text |Cite
|
Sign up to set email alerts
|

Copper Corrosion Mechanism in the Presence of Formic Acid Vapor for Short Exposure Times

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 19 publications
5
66
0
3
Order By: Relevance
“…For low relative humidity conditions, it was employed in the desiccator a saturated solution of K 2 CO 3 • 2H 2 O and NH 4 Cl to obtain 40% RH and 80% RH according to the ASTM E104-85 standard. 7 The relative humidity condition near 100% was obtained placing a recipient with 500 mL of propionic acid solution at the bottom of the desiccator.…”
Section: Exposures In Closed Chambermentioning
confidence: 99%
See 3 more Smart Citations
“…For low relative humidity conditions, it was employed in the desiccator a saturated solution of K 2 CO 3 • 2H 2 O and NH 4 Cl to obtain 40% RH and 80% RH according to the ASTM E104-85 standard. 7 The relative humidity condition near 100% was obtained placing a recipient with 500 mL of propionic acid solution at the bottom of the desiccator.…”
Section: Exposures In Closed Chambermentioning
confidence: 99%
“…7 The relative humidity condition near 100% was obtained placing a recipient with 500 mL of propionic acid solution at the bottom of the desiccator. In these experiments the propionic acid vapor was produced, following the procedure described in previous works [2][3][4][5][6][7][8][9] and in any case, solutions were renewed weekly to prevent degradation of the organic compound.…”
Section: Exposures In Closed Chambermentioning
confidence: 99%
See 2 more Smart Citations
“…Graedel 2 finds that the anions of organic acids (acetates and in smaller amount, formates) constitute between 0.1 and 1% of the total ion concentration in the copper patina exposed in outdoor atmospheres by long periods of time. Copper is corroded in presence of organic acids such as formic, acetic and butyric [3][4][5][6][7][8][9][10] . It has been found that the corrossivity of the organic acids vapors in ppmv (parts per million in volume) level on copper is given in the following order (from the highest to the lowest aggressiveness level) acetic > formic > butyric 7,[9][10] .…”
Section: Introductionmentioning
confidence: 99%